2011
DOI: 10.4103/0972-0707.80748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of sealing ability of three different obturation techniques - Lateral condensation, Obtura II, and GuttaFlow: An in vitro study

Abstract: Aim:To evaluate and compare the sealing ability between the conventional cold lateral condensation technique and two different obturating techniques — Obtura II and GuttaFlow under a stereomicroscope at 40× magnification.Materials and Methods:Sixty single-rooted teeth were selected and the canals were shaped with ProTaper rotary files. Irrigation was performed with 5% sodium hypochlorite and 17% EDTA. The teeth were then separated into three groups depending on the type of obturation technique. Group A (n = 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…6 In the present study, the most commonly used and studied technique was lateral condensation because of its easy placement of materials. 7 Thermafil is a carrier-based, thermoplasticized technique described by Johnson. Johnson claimed that the technique was effective in filling all canal spaces and isthmuses.…”
Section: Discussionmentioning
confidence: 99%
“…6 In the present study, the most commonly used and studied technique was lateral condensation because of its easy placement of materials. 7 Thermafil is a carrier-based, thermoplasticized technique described by Johnson. Johnson claimed that the technique was effective in filling all canal spaces and isthmuses.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,21,22 Instead of longitudinal section, a few authors have suggested transverse sectioning of the roots at predetermined distances from the apex to assess the dye penetration at each level. 23,24 Transverse sectioning is considered as more damaging than longitudinal sectioning. Although it allows a better visualization of the dye penetration, the objective measurement of dye penetration in these sections is more difficult to measure with accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 La técnica de cono único en frío, por el contrario, está siendo ampliamente usada en nuestro medio debido a su facilidad y bajos costos, sin importar que se logre o no el sellado tridimensional del conducto radicular, lo cual va en contraposición a la evidencia, que ha demostrado que esta técnica presenta altos índices de fracaso debido a su falta de sellado. [7][8][9][10] La filtración con tintes y la filtración microbiana son los dos métodos más comunes para evaluar la microfiltración de obturaciones endodónti-cas, 11 pero la filtración microbiana es el método más relevante, ya que se ajusta a las condiciones clínicas. En nuestra investigación se usó la técnica de doble cámara, método que fue introducido por primera vez por Torabinejad y colaboradores 12 (Figura 1).…”
Section: Introductionunclassified
“…5,6 The cold single-cone technique, on the contrary, is being widely used nowadays due to its simplicity and low cost, even though it does not provide a threedimensional sealing of the root canal, in contrast to the evidence, which has demonstrated that this technique has high failure rates due to poor sealing. [7][8][9][10] Dye penetration and microbial filtration are the two most common methods to evaluate microleakage of endodontic obturations, 11 but microbial filtration is the most relevant method, since it fits clinical conditions. This study used the dual chamber technique, a method that was first introduced by Torabinejad et al 12 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%